2016
DOI: 10.1136/bmjopen-2016-011301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of religious involvement on cognition from a life-course perspective: protocol for a systematic review and meta-analysis

Abstract: IntroductionPreserving cognitive health is a crucial aspect of healthy ageing. Both abnormal and normal cognitive decline can adversely affect the health of ageing populations. Evidence suggests religious involvement (RI) can preserve cognition in ageing populations. The primary purpose of this review is to examine the evidence regarding the association between RI and cognition from a life-course perspective.Methods and analysisThis systematic review and meta-analysis has been registered with PROSPERO (registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…A previous longitudinal study among older Mexican Americans also found that religiously active elders had lower rates of CD than the religiously inactive . Reportedly, participation in religious organizations can preserve cognition through a soothing outlet, which may be protective against physiological changes such as elevated blood cortisol, caused by stress, anxiety, and depression . These physiological changes may negatively influence certain mechanisms of the brain that are responsible for memory .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A previous longitudinal study among older Mexican Americans also found that religiously active elders had lower rates of CD than the religiously inactive . Reportedly, participation in religious organizations can preserve cognition through a soothing outlet, which may be protective against physiological changes such as elevated blood cortisol, caused by stress, anxiety, and depression . These physiological changes may negatively influence certain mechanisms of the brain that are responsible for memory .…”
Section: Discussionmentioning
confidence: 93%
“…41 Reportedly, participation in religious organizations can preserve cognition through a soothing outlet, which may be protective against physiological changes such as elevated blood cortisol, caused by stress, anxiety, and depression. 42 These physiological changes may negatively influence certain mechanisms of the brain that are responsible for memory. 43 Spirituality can also stimulate the higher cortical functions related to abstract thinking (eg, meaning in life, morality, and transcendence), which may result in delaying cognitive deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…This result reflects the beneficial effects of religiosity on cognitive functions, in accordance with previous longitudinal studies that suggest religiosity to be a protective factor against cognitive decline. [8][9][10][11][12][13][14][15][16] Using structural equation modeling, we identified the beneficial effect of religiosity on cognitive functions with crosssectional data. Further, the findings of this study demonstrate that the beneficial effects could vary depending on the subdomains of religiosity.…”
Section: Discussionmentioning
confidence: 99%
“…13 These results suggest that religious affiliation seems to be a protective factor, not only for physical health but also for cognitive functions. 14,15 However, these studies have a limitation in that they have evaluated cognitive functions based on a single composite score or global cognitive function scale (eg, MMSE, the clinical dementia rating). [8][9][10]12,13 There are various subdomains under cognitive functions such as memory, language, and constructive ability.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review of the effect of religious and spiritual involvement on cognitive function from 2019, 82% of the research articles reported positive associations between religious involvement, spirituality, and brain health. According to the above-noted systematic review, religious and spiritual involvement appears therefore to be protective against cog-nitive decline in middle and old age adults [ 3, 4 ]. The opposite appears to be true as well.…”
Section: Introductionmentioning
confidence: 99%